Recreation & willingness to travel / Muhammad Azizi Abdullah, Mohamad Afiq Abd Hanem and Muhammad Asyraf Mohd Yusof - Abdullah, Muhammad Azizi (2016)
This paper is concerned with examining the length of distance recreational visitor travel in order to engage in recreational activities and factors that contributes to the decision. Recreational activities is one way to enhance a healthy lifestyle and coupled by fun activities and good facilities can convince visitors to come for recreational activities despite a considerable distance. The motivation and experience of visitor participate in recreational activities is foundational to identifying the distance visitor willingness to travel to recreational centre. The advantages of this study is to find out in more detail that the travel distance can also influence the decision to visit the recreation centre as compared to the time and cost. This study uses quantitative methods to understand the demographic of visitor and the number of visitors interested in recreational activities outside their area. The result show the visitor encourage to travel far outside the state to the recreational centre because suits with the activities preference. From a practical perspectives, the study offers important implication for destination marketers to enhance the visitor to recreational centre.